Population pharmacokinetics of belantamab mafodotin, a BCMA‐targeting agent in patients with relapsed/refractory multiple myeloma. (29th July 2021) - Rathi, Chetan; Collins, Jon; Struemper, Herbert; Opalinska, Joanna; Jewell, Roxanne C.; Ferron‐Brady, Geraldine
Abstract: Belantamab mafodotin (belamaf) is an antibody–drug conjugate (ADC) targeting B‐cell maturation antigen (BCMA). Nonlinear mixed‐effects models were developed to characterize the population pharmacokinetics (PopPK) of ADC, total monoclonal antibody (mAb), and cysteine‐maleimidocaproyl‐MMAF (cys‐mcMMAF) after 0.03–4.6 mg/kg dosing every 3 weeks in heavily pretreated patients with relapsed/refractory multiple myeloma (RRMM; DREAMM‐1, n = 73; DREAMM‐2, n = 218). Sequential modeling methodology was used. Individual post hoc parameter estimates from the final ADC model were used to develop total mAb and cys‐mcMMAF models. Formal covariate selection used a modified stepwise forward inclusion method with backward elimination. A linear, two‐compartment PopPK model with a time‐varying clearance (CL) described ADC PK. Initial ADC typical value for CL for a DREAMM‐2 patient was 0.936 L/day with a half‐life of 11.5 days, over time CL was reduced by 28% resulting in a half‐life of 14.3 days. Time to 50% maximal CL change was 50 days. Baseline soluble BCMA (sBCMA), immunoglobulin (IgG), albumin, and bodyweight impacted ADC CL. Cys‐mcMMAF concentrations were described with a linear two‐compartment model linked to ADC; input rate was governed by deconjugation/intracellular proteolytic degradation of ADC represented by an exponentially decreasing MMAF:mAb (drug antibody ratio [DAR]) after each dose. Time to 50% DAR reduction was 10.3 days. Baseline sBCMA and IgG impacted cys‐mcMMAF central volume of distribution. In conclusion, ADC, total mAb, and cys‐mcMMAF concentration–time profiles in RRMM were well‐described by PopPK models, and exposure was most strongly impacted by disease‐related characteristics.